2003
DOI: 10.1074/jbc.m302096200
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated Invasion of Staphylococcus aureus into Human Cells Requires Src Family Protein-tyrosine Kinases

Abstract: Staphylococcus aureus, a common cause of nosocomial infections, is able to invade eukaryotic cells by indirectly engaging ␤ 1 integrin-containing host receptors, whereas non-pathogenic Staphylococcus carnosus is not invasive. Here, we identify intracellular signals involved in integrin-initiated internalization of S. aureus. In particular, the host cell actin cytoskeleton and Src family protein-tyrosine kinases (PTKs) are essential to mediate S. aureus invasion. Src PTKs are activated in response to pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 39 publications
2
113
2
2
Order By: Relevance
“…3B). A similar pattern of invasiveness has been observed before using antibiotic protection assays and antibody-dependent staining procedures (Agerer et al, 2003), indicating that the covalent modification of S. aureus by FITC and biotin does not impair the integrin-mediated internalisation process. Taken together, these results demonstrate that the novel antibody-independent FBA staining procedure is a convenient and reliable technique for distinguishing between extracellular and intracellular bacteria.…”
Section: Fba Staining Of Gram-positive S Aureussupporting
confidence: 82%
See 2 more Smart Citations
“…3B). A similar pattern of invasiveness has been observed before using antibiotic protection assays and antibody-dependent staining procedures (Agerer et al, 2003), indicating that the covalent modification of S. aureus by FITC and biotin does not impair the integrin-mediated internalisation process. Taken together, these results demonstrate that the novel antibody-independent FBA staining procedure is a convenient and reliable technique for distinguishing between extracellular and intracellular bacteria.…”
Section: Fba Staining Of Gram-positive S Aureussupporting
confidence: 82%
“…Previously, we and others have demonstrated that S. aureus is able to exploit fibronectin and host cell h1 integrins to gain access to an intracellular compartment, whereas the related nonpathogenic species S. carnosus does not invade eukaryotic cells (Sinha et al, 1999;Fowler et al, 2000;Agerer et al, 2003). Therefore, we labelled both species of staphylococci with FITC and biotin and then infected 293 cells for 2 h. Again, processing of the fixed samples according to the FBA staining procedure resulted in a clear discrimination between extracellular and intracellular bacteria (Fig.…”
Section: Fba Staining Of Gram-positive S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysis immunoprecipitation, Western blotting, and gelatine zymography. Cells were solubilized in a modified RIPA lysis buffer containing 1% Triton X-100, 1% sodium deoxycholate, and 0.1% SDS [20]. Immunoprecipitations, SDS-PAGE, Western blotting, and gelatine zymography were performed as described [19,21].…”
Section: Methodsmentioning
confidence: 99%
“…Fn then serves as a molecular link connecting the bacteria with the principal host cell fibronectin receptor, the integrin a 5 h 1 (Fowler et al, 2000). Previously, we and others have observed that FnBP-initiated uptake via integrin a 5 h 1 is the major route of S. aureus internalization in vitro (Sinha et al, 1999;Sinha et al, 2000;Agerer et al, 2003). Therefore, S. aureus and the nonFn-binding, non-pathogenic S. carnosus were labelled with CFSE and used to infect fibroblasts isolated from integrin h1-deficient mouse embryos (GD25 cells) as well as GD25 cells stably expressing human integrin h1 (Fig.…”
Section: Evaluation Of Integrin-dependent Invasion Of S Aureus By Flmentioning
confidence: 98%